Respuesta :
Answer: The simplified value of the given radical expression is [tex]2\sqrt2.[/tex]
Step-by-step explanation: We are given to simplify the following radical expression :
[tex]E=3\sqrt2-\sqrt2~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We know that for a radical expression with similar radicals, the following property holds :
[tex]a\sqrt b-d\sqrt b=(a-d)\sqrt b.[/tex]
So, from equation (i), we get
[tex]E\\\\=3\sqrt 2-\sqrt 2\\\\=(3-1)\sqrt2\\\\=2\sqrt2.[/tex]
Thus the required simplified value of the given radical expression is [tex]2\sqrt2.[/tex]